Design and Development of a Trailed Type Transplanter for Oil Palm Seedling - El Pebrian, Darius (2002)
A trailed type transplanter that runs by a 4-wheel tractor with at least 63.4 kW for field transplanting of oil palm seedlings had been designed, developed and tested. AutoCAD 2000 software was used to produce the 3-D conceptual design of the proposed machine system. Computations were made to determine required total hydraulic pressure to operate all actuators within the hydraulic system of the transplanter. The machine configuration consists of the main chassis, seedling bin, seedling planting assembly, operator compartment, and associated hydraulic system. Two operators are required in the involved transplanting operation; a driver for the tractor and an operator for transplanter. The driver drives the tractor-transplanter in the field while the operator on the transplanter operates the hydraulic control system to integrate all operational activities. The involved operational activities includes the preparations of planting hole, placement of seedling in the prepared hole, covering of the seedling in the prepared hole, and compacting of the soil around the planted seedling. An area size of 200 m length and 56 m width at the university farm was chosen to be the test plot for the five days field evaluations duration. A special time and motion study was conducted on the 6th day of the field evaluation to include additional activity concerning removal of plastic polybag from seedling before planting. The test plot soil is from Serdang series with sandy clay loam texture classification. A triangular planting pattern with density of 160 palms/ha, planting distance of 850 cm and row distance of 736 cm were employed in the test plot.